2009
DOI: 10.1016/j.bcp.2009.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling identifies novel key players involved in the cytotoxic effect of Artesunate on pancreatic cancer cells

Abstract: Pancreatic cancer is one of the most aggressive human malignancies, with an extremely poor prognosis. The paucity of curative therapies has translated into an overall 5-year survival rate of less than 5%, underscoring a desperate need for new therapeutic options.Artesunate (ART), clinically used as anti-malarial agent, has recently revealed remarkable anti-tumor activity. However, the mechanisms underlying those activities in pancreatic cancer are not yet known. Here we evaluated the antitumor activity of Arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 44 publications
3
74
0
3
Order By: Relevance
“…Our findings also agree with authors who assessed the genotoxic effects of other sesquiterpenes (Burin et al, 2001;Canalle et al, 2001;Al-Zubairi et al, 2010). In addition to causing DNA damage, the cytotoxicity of these substances, especially artemisinin, is due in part to the decreased expression of topoisomerase 2 (Youns et al, 2009), which is essential for cell proliferation and is expressed in dividing cells (Toyoda et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings also agree with authors who assessed the genotoxic effects of other sesquiterpenes (Burin et al, 2001;Canalle et al, 2001;Al-Zubairi et al, 2010). In addition to causing DNA damage, the cytotoxicity of these substances, especially artemisinin, is due in part to the decreased expression of topoisomerase 2 (Youns et al, 2009), which is essential for cell proliferation and is expressed in dividing cells (Toyoda et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Hou et al (2008) reported that artemisinin and artesunate exerted the greatest cytotoxicity on HepG2, inhibiting cell proliferation and inducing apoptosis by activating the CASP3 gene. Other authors also observed similar effects for both of these compounds (Li et al, 2008;Youns et al, 2009;Du et al, 2010;Zhang et al, 2010). We analyzed expression of the CASP3 gene in HepG2 cells after exposure to artemisinin and artesunate because it is the final common pathway of almost all apoptotic pathways.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Recently, tumor therapy by traditional Chinese herb is becoming more and more attractive (He et al, 2008;Youns et al, 2009;Chen et al, 2010). We therefore attempted to examine the effects of triptolide and artesunate on pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Cell Cycle and Apoptosis of OS Cells by Flow Cytometer Assays Cells treated as described were fixed with 95% ethanol, washed with cold PBS and incubated with 150 mL of hypotonic fluorochrome solution, as previously described, 20) in the dark at 4°C overnight. The apoptotic cells were stained using a CF488A-Annexin V and Propidium Iodide Apoptosis Assay Kit (Biotium), according to the protocols of the kit.…”
Section: Reagentsmentioning
confidence: 99%